Prognostic factors of early-onset otitis media with effusion in children treated using tympanostomy. (2nd August 2021) - Inoue, Maki; Yamamoto, Kouji; Hirama, Mariko; Ogahara, Noboru; Takahashi, Masahiro; Oridate, Nobuhiko
Abstract: Background: Predicting the prognosis of early-onset otitis media with effusion (OME) in children is difficult. Objectives: To investigate the prognostic factors of OME in children undergoing tympanostomy at 1 year of age. Material and methods: We examined 66 children (123 ears) followed up to 6 years of age. OME prognosis was determined by a history of re-tympanostomy at the last examination. We retrospectively analysed the prognostic factors based on the duration of first ventilation tube (VT) placed, history of otorrhea, asthma, adenoidectomy, and mastoid air cell system (MACS) size at 1 year before tympanostomy and at 3 years. Results: While 25 ears underwent re-tympanostomy (group 1), 98 did not (group 2). The mean duration of VT placed was 21 months and 25, and the mean MACS size at 3 years was 314 mm 2 and 441, respectively, in the corresponding groups. MACS size at 3 years was significantly smaller in group 1 than in group 2. The combination of MACS size at 3 years and duration of VT placed showed the best value of area under the curve. Conclusion and significance: The most probable prognostic factor was the combination of the MACS size at 3 years and duration of VT placed.